Relationship between retention intention, perceived organizational support, and medical narrative ability among nurses: a cross-sectional multi-center study - Li, Yanjia; Zhang, Rong; Kang, Limei; Ma, Guoting (Frontiers in Health Services, 2025)
BackgroundMNA is widely regarded as an important factor in promoting the construction of humanistic hospitals. Nurses are the medical professionals who have the highest participation in the clinical practice of narrative medicine and humanistic nursing in hospitals. Therefore, it is crucial to study the impact of nurses’ RI and POS on MNA.ObjectivesThis study aims to determine the effects of nurses’ perceived organizational support (POS) and retention intention (RI) on nurses’ medical narrative ability (MNA) and to reveal the mediating role of RI in the possible impact.MethodsA cross-sectional descriptive correlational study was performed. Survey data were gathered from 1,831 practicing nurses working in eight tertiary general hospitals across China. The questionnaire was divided into four sections: a sociodemographic characteristics survey, a medical narrative ability scale, a perceived organizational support scale, and a Chinese questionnaire for nurses’ intention to remain employed. Data analysis was conducted using SPSS 27.0.ResultsThe survey results show that the relationships among RI, POS, and MNA are all significant, with correlation coefficients ranging from 0.344 to 0.468. The indirect effect of POS on MNA is 1.267, accounting for 29.12% of the cumulative effect.ConclusionThis study reveals that nurses’ POS not only directly enhances their MNA but also indirectly has a profound impact on this ability through the mediating mechanism of the RI. This finding indicates that nursing managers both domestically and internationally should pay close attention to nurses’ perception levels of organizational support and their RI, and formulate precise and effective intervention strategies, thereby using this as a potential organizational management approach to enhance nurses’ MNA.